Moving Forward from Singapore - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed giving the poor people of the world a chance to escape poverty. He spoke about the actions to promote good governance that are crucial to successful economic development, poverty reduction and helping member countries achieve the Millennium Development Goals. He mentioned issues of global import, particularly the prospects for the Doha Round and the issue of clean, efficient, and affordable energy. He concluded by saying that the Bank Group will continue to remain active in a variety of international efforts to provide global public goods.